Interrupting the legal person - Sarat, Austin (Emerald Publishing Limited, 2022)
This special issue is part one of a two-part edited collection on interrupting the legal person, and what this means. Should we think of the legal person as a technical and grammatical question that varies across different legal traditions and jurisdictions? Does this cut across different ways of living and speaking law? The chapters in this volume interrogate the role of the person and personhood in different contexts, jurisdictions, and legal traditions. This volume is an appealing read for anyone interested in rich contemporary conversations around legal personhood, and in interrupting and interrogating assumptions which we may take for granted.
Keywords: Juristic persons.; Law -- Civil Law.; Private -- Civil law: general works.; elektronické knihy; electronic books